A probabilistic model including constraint and plastic strain effects for fracture toughness predictions in a pressure vessel steel. (December 2016) - Ruggieri, Claudio
Abstract: This work describes a probabilistic model based upon a local failure criterion incorporating the potential effects of plastic strain on cleavage fracture coupled with the statistics of microcracks. A central objective is to explore and further extend application of a multiscale methodology incorporating the influence of plastic strain on cleavage fracture phrased in terms of a modified Weibull stress ( σ ˜ w ) to correct fracture toughness for effects of geometry and constraint loss. Fracture toughness testing conducted on an ASTM A285 Gr C pressure vessel steel provides the cleavage fracture resistance data needed to assess specimen geometry effects on experimentally measured J c -values. Non-linear finite element analyses for 3-D models of fracture specimens with varying geometries provide the relationship between σ ˜ w and J from which the variation of fracture toughness across different crack configurations is predicted. This study shows that the modified Weibull stress methodology effectively removes the geometry dependence of fracture toughness values. Highlights: Introduction and application of a modified Weibull stress incorporating plastic strain effects. Fracture toughness values for an A285 Gr C steel depend strongly on specimen geometry. Marked differences in crack front stresses between PCVN and large SE(B) specimens. Toughness predictions depend strongly on the adopted probabilistic model. The modified Weibull stress model provides good toughness predictions.